Research Methods: A Practical Guide for Students and Researchers (Construction Economics and Building, 2018)
Willie TanResearch Methods: A Practical Guide for Students and ResearchersWorld Scientific Publishing, Singapore, 2017ISBN: 978-981-3229-58-7 (hardcover), ISBN: 978-981-3229-61-7 (softcover). 228 pages